A saúde mental à margem do SUS: experiências de vastidão e confinamento nas práticas clínicas - Endo, Teresa Cristina (2013)
This study records twenty-five years of experience working in the public health of the city of São Paulo. The clinical care in the Brasilian Unified Health System (SUS) was the source of the production of fertile clinical narratives for this research. These fragments have allowed me to discuss cases that constitute both the clinical method as the research method. The clinical method guides the practices of this research to the construction of narratives about the clinical cases, besides allow a clinical reflection of this material and the phenomenon under analysis. This work is focused on the subjective position of clinical experience in the obscure that underlies the analytic encounter. Such research requires put the question about the preservation of margins, borders and boundaries on the territories, continuously marked and remarked. These lines show up in the field and in the work of mental health nowadays and they are very similar to the demarcations and categories in force in the past. Users of mental health system seen as marginal from point of view of the system of rights, are still massively kept within the walls of official confinement of the insanity, banished from society, but now outside of the walls. When we find In the SUS so striking separation of bodies, spaces of distinction and demarcation of places, still in force, it is evident the urgency to inquire about the function of this clinical position, its foundations and the basic assumptions which maintains frequently separate the suffering of pathos from the conditions to establish otherness